Cardiac structure and function in cyclists and runners. Comparative echocardiographic study. Issue 2 (August 1984) - Fagard, R; Aubert, A; Staessen, J; Eynde, E V; Vanhees, L; Amery, A
Abstract : Twelve cyclists and 12 long distance runners matched for age, height, and weight with two control groups of 12 non-athletes were studied echocardiographically to evaluate cardiac structure and function. Runners weighed 8 kg less than cyclists, but age and height were similar. Peak oxygen uptake per kg body weight was higher in athletes than in the control subjects but was similar in the cyclists and in the runners. The athletes' hearts had a larger end diastolic left ventricular internal diameter, mean wall thickness, and cross sectional area of the left ventricular wall than those of the respective control subjects. Nevertheless, whereas the left ventricular internal diameter was not different between the cyclists and runners, mean wall thickness and cross sectional area of the left ventricular wall were greater in the cyclists even after adjustment for weight. The ratio of wall thickness to left ventricular internal radius was significantly larger in cyclists than in their control group, but the ratio was similar in runners and their control group. The echocardiographic indices of left ventricular function were similar in the athletes and the control groups. Systolic left ventricular meridional wall stress was lower in the cyclists than in the runners. The data suggest that runners develop an increase in left ventricular wall thickness which is proportionate to the internal diameter but that in cyclists the increase is disproportionate because of the isometric work of the upper part of the body during cycling.